Perancangan Solo Pet Center Sebagai Sarana Edukasi dan Rekreasi Keluarga - Mamik Wijayanti, Rindu; , MS Priyono Nugroho, ST, MT; , Suryaning Setyowati, ST. MT (2015)
Pet Center is a place that provides all sorts associated with pets ranging from equipment and needs of the animal, the animal care and animal health. Some facilities available in Pet center is usually a pet shop, pet hotels, pet grooming and pet clinics, but in Solo themselves some of these facilities are not located in one place. Based on these problems, the authors will design a vessel that can accommodate all the activities of the animals contained in one place that consists of pet shop, pet hotels, pet grooming, pet clinic, pet training activities, animal competitions and several other supporting facilities. In addition, also in the city of Solo was still a little for tourism-related esukasi about animals, then the Pet Center is to increase tourism related about animals (pets). In line with new ideas and hopefully in time writer Solo Pet Center can be useful and beneficial for the animals, animal lovers as well as those common in the city of Solo